PENDAMPINGAN PENESEHAT HUKUM BAGI ANAK YANG BERKONFLIK DENGAN HUKUM - Ariadi, Agus (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to determine the legal application of child offenders in conflict with the law at the level of investigation, prosecution and trial in the Unaaha District Court and what are the legal consequences if a child offender is in conflict with the law if not accompanied by a legal advisor in a Case Study Number 8 / Pid.Sus-Anak / 2017 / PN. This research is a normative legal research that is perspective with a legislative approach and a case approach. The type of data used is secondary data. Secondary data sources used include primary legal materials and secondary legal materials. Data collection techniques used are literature study techniques. The analysis technique used in this study is a syllogism method that uses deductive thinking patterns. The results of this study indicate that the Child Criminal Justice System Law requires mentoring legal counsel by looking at the subject of the perpetrator, which means that all children in conflict with the law with any indictment must be accompanied by advocates or other legal aid providers. law if it is not fulfilled. Law No. 11 of 2012 has closed the gap for judges / judges to examine cases of child defendants who are not being accompanied by lawyers or other legal aid providers.